Revitalization Of The People's Economy Through The Red And White Cooperative Ecosystem - Pardomuan Robinson Sihombing (International Journal of Economics, Science, and Education, 2026)
This study presents a critical, in-depth, and comprehensive analysis of the policy architecture, business model, and strategic implications of the Red and White Cooperative (KMP) program launched by the Government of Indonesia for the 2024-2029 period as the central pillar of people's economic transformation. Under the legal umbrella of Presidential Instruction Number 9 of 2025, this program targets the establishment and revitalization of 80,000 cooperative units as rural economic aggregators, vitally integrated with the Free Nutritious Meal Program (MBG). This study uses a qualitative approach, with a policy case study design, enriched by a systematic literature review and a global comparative analysis. The analysis was conducted through a multi-theoretical lens that included New Institutional Economics to dissect the structure of transaction costs; Institutional Isomorphism from DiMaggio and Powell to evaluate regulatory pressures and the risks of uniformity without substance; Stewardship Theory for aspects of managerial motivation; and the concept of Platform Cooperativism to examine digital sovereignty. The study's findings show that integrating KMP as a Nutrition Fulfillment Service Unit (SPPG) creates a captive market, which is crucial for initial cash flow. However, risk analysis reveals the potential for coercive isomorphism, which can give rise to "shell cooperatives" if it is not accompanied by strengthened social capital and member autonomy. Comparative studies of the Zen-Noh federation model in Japan and the Mondragon Corporation innovation ecosystem in Spain recommend restructuring from an atomistic model to a strong vertical federation, as well as the institutionalization of cooperative education to ensure long-term sustainability free from state dependence